2006
DOI: 10.1007/s10453-006-9032-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary survey of indoor and outdoor airborne microfungi at coastal buildings in Egypt

Abstract: Forty six species and two sterile fungi and yeast species were isolated from samples collected both indoors and outdoors of coastal buildings located in an Egyptian coastal city. Twenty flats from ten buildings were investigated; children living in these buildings have been reported to suffer from respiratory illnesses. Samples were taken using a New Brunswick sampler (model STA-101) operating for 3.0 min at a flow rate of 6.0 l/min. Most of the species isolated have been associated with symptoms of respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 55 publications
4
21
1
Order By: Relevance
“…The most commonly reported airborne bacteria genera are Bacillus, Micrococcus, Staphylococcus, and Pseudomonas (Mancinelli and Shulls 1978;Shaffer and Lighthart 1997), whereas Cladosporium, Alternaria, Penicillium, Aspergillus species dominate the fungal composition of outdoor atmospheric environments (El-Morsy 2006;Fang et al 2005). The concentration of microbes in the air is affected by several factors, including daily and seasonal meteorological variations, vegetation, air pollution, agricultural, industrial, and other human activity (Klaric and Pepeljnjak 2006;Levetin and Dorsey 2006;Lin and Li 2000;Pasanen 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported airborne bacteria genera are Bacillus, Micrococcus, Staphylococcus, and Pseudomonas (Mancinelli and Shulls 1978;Shaffer and Lighthart 1997), whereas Cladosporium, Alternaria, Penicillium, Aspergillus species dominate the fungal composition of outdoor atmospheric environments (El-Morsy 2006;Fang et al 2005). The concentration of microbes in the air is affected by several factors, including daily and seasonal meteorological variations, vegetation, air pollution, agricultural, industrial, and other human activity (Klaric and Pepeljnjak 2006;Levetin and Dorsey 2006;Lin and Li 2000;Pasanen 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In several aeromycological studies and in agreement with the current results, Cladosporium was considered as one of most abundant genera, if not, the most, abundant one reported all over the world such as Egypt (Moubasher & Moustafa 1974, El-Sherbeny 1987, Moubasher 1993, Ismail et al 2002, Hellwan area, Egypt (Abdel Hameed et al 2009), banana field in Qena (El-Said & Abdel-Hafez 1995), Uganda (Ismail et al 1999), USA (Lacey 1981), Porto (Oliveira et al 2005), Yemen (El-Essawy et al 1992), Doha, Qatar (Al-Subai 2002), Eskisehir and Afyonkarahisar, Turkey (Asan et al 2004(Asan et al , O¨zkara et al 2007), Sari and Zanjan, Iran (Hedayati et al 2005, Nourian et al 2007, and Amman and Zarqa area, Jordan (Shaheen 1992, Abu-Dieyeh et al 2010. Cladosporium spores are the dominant aerospora in hot climates (Takahashi 1997, Sen & Asan 2001, Al-Subai 2002, El-Morsy 2006. Cladosporium spores contributed the highest number (26.87% to the total sugarcane fields aerspora) in India (Ahire et al 2010), of aerospora in groundnut fields (47·32%) in Visakhapatnam, India (Mallaiah & Rao 1990), as well as of the aerospora (65·7%) in Hong Kong (Turner 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported that the high percentage of Cladosporium may be attributed by the size of spores and smooth wall which favor and facilitate the transport of airborne spores in sandstorms. A further factor favoring this fungus is due to the spores being highly resistant to hot climates [18,32].…”
Section: Discussionmentioning
confidence: 99%